Concept Analysis of Heat and Temperature in Batik Gedog - Ni’mah, Vika Luthfiyatun; Imamah, Nanda Sofa; Sasmi, Rinda Rahmanisa; Rosyida, Krisna Muftidafila Ilham; Nurlailiyah, Alfi; Suliyanah, Suliyanah (Mitra Edukasi dan Publikasi, 2024)
Batik Gedog, a traditional craft from Tuban Regency, is rich in local wisdom, particularly in its unique manufacturing processes, motifs, and colors. This study aims to analyze the concepts of heat and temperature involved in creating Batik Gedog, demonstrating its potential as a contextual learning medium for teaching these concepts. The research adopts a qualitative descriptive approach, utilizing ethnographic methods to gather insights. Purposive sampling was employed to select Batik Gedog craftsmen with comprehensive knowledge of the Batik-making process. Data collection involved interviews with two craftsmen from Kerek District, Tuban Regency, and a review of relevant literature. The data were analyzed using the Miles and Huberman model. The findings reveal the presence of heat transfer mechanisms—conduction, convection, and radiation—during the Batik-making process, alongside the phase change of Batik wax from solid to liquid through heating. These results underscore the relevance of heat and temperature concepts in the traditional practice of making Batik Gedog.